Outcomes of Primary Simultaneous Pancreas-kidney Transplants by Induction Agent in the United States - Adam Cerise, MD; Tamer Shaker, MD; Phuoc LeNguyen, MD; Anant Dinesh, MD; Karthik Ramanathan, MD; Vanessa Humphreville, MD; Scott Jackson, MS; Raja Kandaswamy, MD; Samy Riad, MD, MS (Transplantation Direct, 2022)
Background. Long-term outcome data by induction type in simultaneous pancreas-kidney (SPK) is limited. Methods. Utilizing the Scientific Registry of Transplant Recipients, we examined all primary SPK transplants between 2000 and 2020, excluding crossmatch-positive recipients. We grouped recipients according to induction regimen into 3 groups: rabbit anti-thymocyte globulin (r-ATG) (n = 5678), alemtuzumab (n = 1199), and interleukin-2 receptor antagonist (IL-2RA; n = 1593). We analyzed the 10-y recipient and composite (kidney and pancreas) graft survival using the Kaplan-Meier survival function. Cox-proportion hazard models were generated to examine the association between induction type, the 10-y recipient, and graft survival. Models were adjusted for recipient age, sex, ethnicity, HLA-mismatch, diabetes type, dialysis dependency, cold-ischemia time, local versus imported organs, panel reactive antibody, steroid maintenance, and Pancreas Donor Risk Index. Results. r-ATG was associated with the lowest 1-y kidney and pancreas rejection rates compared with other agents (P < 0.001). In the univariable analysis, induction type was not associated with recipient (log-rank P = 0.11) or graft survival (log-rank P = 0.36). In the multivariable model for the composite graft survival, alemtuzumab use was associated with 22% increased kidney or pancreas graft loss compared with r-ATG (adjusted hazard ratio, 1.22; 95% confidence interval, 1.05–1.42), whereas IL-2RA use was not a predictor of graft survival. Induction type did not influence recipient survival in the adjusted model. Conclusions. r-ATG use was associated with the lowest SPK rejection rates. Compared with r-ATG, alemtuzumab but not IL-2RA was associated with worse long-term death-censored SPK graft outcome. Our analysis supports the common use of r-ATG for induction in US primary SPK recipients.